Synthesis of epi-Chloranthalactones A, B, D and E - Fenlon, Thomas W.; Jones, Michael W.; Adlington, Robert M.; Lee, Victor (Synlett, 2018)
The synthesis of various epimers of the lindenane class of sesquiterpenes from epi-lindenene, based on a possible biosynthetic hypothesis, is described.
Keywords: sesquiterpenes; chloranthalactones; Aldol reaction; biosynthesis; oxidation